Applying the phononic crystal concept to the intake muffler of a refrigeration compressor. (15th June 2022) - Almeida, V.F.; Lima, V.D.; Arruda, J.R.F.
Highlights: Numerical and experimental methods to evaluate phononic crystal. Methodology to design a phononic crystal. Concept validation. Industrial application on refrigeration area. Abstract: Many previous works explore the creation of wave stop bands (bandgaps) using periodic structures. Aiming at improving the transmission loss of a muffler used in a refrigerant compressor, this work proposes the redesign of an existing intake muffler using the concept of wave attenuation bands caused by Bragg scattering. The challenge consists in designing a phononic crystal (PnC) with bandgaps in the audio frequency range with the size constraints of a practical muffler application. The first part of the research focuses on the development and validation of numerical and experimental techniques to provide guidelines for periodic muffler design. The second part consists in applying the developed concepts and tools to a real compressor muffler following the constraints of the product specifications. A shape optimization technique is used to enlarge the bandgap while keeping the unit cell length in the order of tens of millimeters. Two designs were 3D-printed and tested on the real compressor, reaching 7 dB reduction on the sound power level (SPL) in the aimed frequency band and 4 dB reduction on the overall compressor noise level.